An Empirical Study on The Impact of Macro-Economic Varables on Asian Stock Markets Returns - MARAN K; Padma Prabha C; Mickel Aancy H; VENKATESH P; Senthilnathan C.R (Iranian Journal of Accounting, Auditing & Finance)
The stock exchange is one of the most powerful sectors, which contribute significantly to the economy's wealth. It plays a crucial role in economic growth and economic development, to which industry, trade and trade as a whole would be benefiting. Therefore, a significant number of research projects have been devoted not surprisingly to understanding the nature of stock market movements and their general performance. A number of studies have shown that macroeconomic variables have a significant impact on stock market performance, while other studies have at best found an inconclusive relationship. It is also worth noting that most of these studies were conducted on developed markets and rarely touched on the combination of emerging and developed markets. Hence this study aims at understanding the impact of selected macroeconomic variables such as Export growth, Import growth, Trade balance, Inflation rate, Broad money growth and exchange rate on the stock market chosen Indices of five Asian countries such as India, Japan, China, Hong Kong and Singapore. The Augmented Dickey-Fuller test (ADF), Granger causality test, Johansen cointegration test the short-run and long-run cointegration between the variables. Variance decomposition analysis is also used to determine how much of the variability in stock returns is lagged by its own variance. The study's findings reveal a substantial long-run cointegration among the macroeconomic variables and stock indices in the case of Japan, China, Hong Kong, and Singapore. All the macroeconomic variables are integrated into I (1) except for the trade balance in the case of Japan, which is integrated into I (2).